Designing bi-functional silver delafossite bridged graphene oxide interfaces: Insights into synthesis, characterization, photocatalysis and bactericidal efficiency - Yashas, Shivamurthy Ravindra; Shivaraju, Harikaranahalli Puttaiah; McKay, Gordon; Shahmoradi, Behzad; Maleki, Afshin; Yetilmezsoy, Kaan (ELSEVIER SCIENCE SA, 2021)
The bi-functional nanoscale catalysts are of growing attention to address environmental problems. The present work successfully fabricated the hexagonal silver delafossite oxide bridged graphene oxide ultrathin nanosheets interfaces (AgFeO2/GO) to target photodegradation of an antibiotic and inactivation of model waterborne pathogens for the first time. The AgFeO2/GO composite was prepared via facile hydrothermal treatment followed by ultrasonic agitation by varying the GO loading. The AgFeO2/GO composite and their parent constituents were verified by advanced analytical, microscopic, and spectroscopic techniques like FESEM, EDX, HR-TEM, DLS, XRD, FTIR, XPS, UV-Vis, and PL. The AgFeO2/GO3 composite showed excellent photocatalytic activity towards mineralization of a broad-spectrum antibiotic, lomefloxacin (LMF) under the irradiation of visible light (30 W, LED). A maximum of similar to 88 % of LMF (20 mg/L) was degraded within 75 min of catalysis. The superoxide and hydroxyl radicals were predominant in LMF breakdown. In addition, AgFeO2/GO3 was proved effective up to three consecutive trials retaining 78.85 % efficiency. On the other hand, AgFeO2/GO3 heterojunctions demonstrated fair bactericidal activity against pathogens, Escherichia coli and Staphylococcus aureus. Disc diffusion method of antimicrobial assay confirmed the activity of AgFeO2/GO3 on par with standard drugs. Therefore, in both the functionalities, the GO incorporation along with AgFeO2 standpoints enhanced photoactivity and catalytic inactivation making it a sought-after, bi-functional, and efficient environmental catalyst.
Keywords: Delafossite oxide; Nanocomposite; Bi-functional material; Photodegradation; Antibacterial activity; Antibiotic degradation; FACILE SYNTHESIS; ANTIMICROBIAL ACTIVITY; DEGRADATION; AGFEO2; ANTIBACTERIAL; NANOPARTICLES; WATER; HETEROJUNCTION; PERFORMANCE; Engineering